PENENTUAN SYARAT PADA PERTENGAHAN PERJANJIAN DALAM JUAL BELI KREDIT PERALATAN PERTANIAN - Yitndra, M Saydinal; Lubis, Ramiah; Fauzia, Fauzia (Program Studi Muamalah Fakultas Syariah dan Hukum, 2024)
Buying and selling as a means of getting goods easily. Buying and selling credit is a sale and purchase transaction carried out by the community using the payment in installments (installments). Such as buying and selling credit carried out by villagers Payo Bay, Banyuasin district. The concept of buying and selling on credit is the element of time, element of risk, element of submission, element of trust, and element of approval. Buy and sell This credit helps the residents of Teluk Payo village. They can buy agricultural equipment by paying it off because they don't have enough money if buying in cash. By buying equipment for farming. This certainly makes it easier for them to farm and the results will be more Good.In writing a thesis using field research (field research) because this research was carried out in the field, namely about the practice of buying and selling credit agricultural equipment in Teluk Payo Village, Banyuasin Regency. As for analyzing the author's data using primary and secondary data methods, ie the method of analysis describes a situation or area of a particular population directly factual. Conclusions that can be drawn from the writing of this thesis is the result of the study, it can be concluded that in the practice of buying and selling credit this agricultural equipment there is a discrepancy that occurs between the parties involved, namely the additional of the amount of money that was not agreed upon. Which one This discrepancy occurs because of the failure of these farmers in farming. That application of intermediate conditions in the financing of agricultural equipment in the village Payo Bay, Banyuasin Regency is not yet fully following the principles of sharia economic law. This can be seen from several conditions that still violate sharia principles, such as adding a certain amount of money to maximize profit.